Vertebral column regionalisation in Chinook salmon, Oncorhynchus tshawytscha - De Clercq, A. (John Wiley and Sons Inc., 2017)

(untitled) (J Anat)
Teleost vertebral centra are often similar in size and shape, but vertebral‐associated elements, i.e. neural arches, haemal arches and ribs, show regional differences. Here we examine how the presence, absence and specific anatomical and histological characters of vertebral centra‐associated elements can be used to define vertebral column regions in juvenile Chinook salmon (Oncorhynchus tshawytscha). To investigate if the presence of regions within the vertebral column is independent of temperature, animals raised at 8 and 12 °C were studied at 1400 and 1530 degreedays, in the freshwater phase of the life cycle. Anatomy and composition of the skeletal tissues of the vertebral column were analysed using Alizarin red S whole‐mount staining and histological sections. Six regions, termed I–VI, are recognised in the vertebral column of specimens of both temperature groups. Postcranial vertebrae (region I) carry neural arches and parapophyses but lack ribs. Abdominal vertebrae (region II) carry neural arches and ribs that articulate with parapophyses. Elastic‐ and fibrohyaline cartilage and Sharpey's fibres connect the bone of the parapophyses to the bone of the ribs. In the transitional region (III) vertebrae carry neural arches and parapophyses change stepwise into haemal arches. Ribs decrease in size, anterior to posterior. Vestigial ribs remain attached to the haemal arches with Sharpey's fibres. Caudal vertebrae (region IV) carry neural and haemal arches and spines. Basidorsals and basiventrals are small and surrounded by cancellous bone. Preural vertebrae (region V) carry neural and haemal arches with modified neural and haemal spines to support the caudal fin. Ural vertebrae (region VI) carry hypurals and epurals that represent modified haemal and neural arches and spines, respectively. The postcranial and transitional vertebrae and their respective characters are usually recognised, but should be considered as regions within the vertebral column of teleosts because of their distinctive morphological characters. While the number of vertebrae within each region can vary, each of the six regions is recognised in specimens of both temperature groups. This refined identification of regionalisation in the vertebral column of Chinook salmon can help to address evolutionary developmental and functional questions, and to support applied research into this farmed species.